2015
DOI: 10.1186/s13569-015-0033-z
|View full text |Cite
|
Sign up to set email alerts
|

Older soft tissue sarcoma patients experience increased rates of venous thromboembolic events: a retrospective cohort study of SEER-Medicare data

Abstract: BackgroundVenous thromboembolic co-morbidities can have a significant impact on treatment response, treatment options, quality of life, and ultimately, survival from cancer. There is a dearth of published information on venous thromboembolic co-morbidity among older soft tissue sarcoma patients.MethodsSEER-Medicare linked data (1993–2005) was utilized for this retrospective cohort analysis (n = 3,480 soft tissue sarcoma patients). Non-cancer patients were frequency-matched by age to cancer patients at a ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Interestingly, patients with soft tissue disease (as opposed to bony) were also more likely to demonstrate TEG-defined hypercoagulability. Prior evidence has established that there is an increased VTE prevalence among patients with soft tissue sarcoma compared with age-matched patients without cancer [22]. However, other studies have not found a difference in VTE rates between patients with bone and soft tissue sarcoma [4, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with soft tissue disease (as opposed to bony) were also more likely to demonstrate TEG-defined hypercoagulability. Prior evidence has established that there is an increased VTE prevalence among patients with soft tissue sarcoma compared with age-matched patients without cancer [22]. However, other studies have not found a difference in VTE rates between patients with bone and soft tissue sarcoma [4, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly sarcoma patients often present with significant comorbidities [7], including cardiovascular (e.g. hypertension, ischemic heart disease, venous thromboembolic events) [5,8,9], renal, and respiratory disease [10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently widely used perforator flaps include anterolateral femoral flap, radial artery perforator flap, ulnar artery perforator flap, peroneal artery perforator flap and posterior tibial artery perforator flap. Among them, the posterior tibial artery and peroneal artery perforator flaps are good choices for repairing soft tissue defects in the distal leg and ankle [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%